A Román-Bánság demográfiai és etnikai viszonyainak változása : 1910-2002 - Kókai, Sándor (Közép-Európai Közlemények, 2012)
The Bánság was a unique cultural area in the historical Hungary, since then it mostly disappeared as the ethnical and linguistic rate changed. The Bánság was the model of peaceful coexistence between 1718 and 1918. Nowadays the maintenance of intercultural heritage is in danger. The region lost the multilingual character, which would mean connection with West-Europe. The depth (settlement level), wide spectrum (609 settlements involving every nationality) and the method of the analysis (mapping the majorities and minorities in the ethnicity) enable objective summarization and complex analysis. The increasing of the population and the formation of the ethnic and settlement space structure was disturbed only temporarily by the World War II. Today, the Bánság region is maybe born again. There is a new form of organization. They are looking for a place in the new globalizing world. They are ready to work together their neighbours. They are looking for all the connection system which was very strong on the historical time. They can do only this way, the development way, because there are different kinds of ethnic and they can get help by this way.